Expression of immunoglobulin-T-cell receptor chimeric molecules as functional receptors with antibody-type specificity. - Gross, G (1989)
To design and direct at will the specificity of T cells in a non-major histocompatibility complex (MHC)-restricted manner, we have generated and expressed chimeric T-cell receptor (TcR) genes composed of the TcR constant (C) domains fused to the antibody's variable (V) domains. Genomic expression vectors have been constructed containing the rearranged gene segments coding for the V region domains of the heavy (VH) and light (VL) chains of an anti-2,4,6-trinitrophenyl (TNP) antibody (SP6) spliced to either one of the C-region gene segments of the alpha or beta TcR chains. Following transfection into a cytotoxic T-cell hybridoma, expression of a functional TcR was detected. The chimeric TcR exhibited the idiotope of the Sp6 anti-TNP antibody and endowed the T cells with a non-MHC-restricted response to the hapten TNP. The transfectants specifically killed and produced interleukin 2 in response to TNP-bearing target cells across strain and species barriers. Moreover, such transfectants responded to immobilized TNP-protein conjugates, bypassing the need for cellular processing and presentation. In the particular system employed, both the TNP-binding site and the Sp6 idiotope reside almost exclusively in the VH chain region. Hence, introduction into T cells of TcR genes containing only the VHSp6 fused to either the C alpha or C beta was sufficient for the expression of a functional surface receptor. Apparently, the VHC alpha or VHC beta chimeric chains can pair with the endogenous beta or alpha chains of the recipient T cell to form a functional alpha beta heterodimeric receptor. Thus, this chimeric receptor provides the T cell with an antibody-like specificity and is able to effectively transmit the signal for T-cell activation and execution of its effector function.